Violation and Satisfaction. A Sociology of Law Study of Non-Pecuniary Damages to Victims of Crime - Dahlstrand, Karl (Lund University, 2016)
The thesis takes its starting point in the question of how damages for violation of crime is determined. This type of non-pecuniary damages to crime victims has a fundamental uncertainty regarding the computation of damages and what is really meant by “violation” in the meaning of the law. There is also a gliding between the violation and the suffering, as to which the compensation is related. The violation-dimension has a more “objective” connotation as a sanction in the sense of an attack on a protected interest within the rule of law. Whereas the suffering-dimension focuses more on the “subjective”, individualized injury as the object of attack. According to law, damages for violation should be determined such that it reflects the present social norms within society. Therefore, the compensation must be seen in relation to the context of criminal law, levels of punishment, the proportionality of the compensation in relation to the punishment and the crimes’ penal value. Thus before the empirical study, two central suppositions were: (1) if the applicator of the law “succeeds” in this task and (2) if it is possible to say something about if the application of the law, for instance the compensation levels, influences the satisfaction among the victims. The general object of the thesis is: to investigate how the application of the law reflects the sense of justice and how empirical knowledge can contribute to the legal field in question.

The study includes two surveys, one involving the public and the other involving crime victims that had received compensation for criminal injuries from the Crime Victim Compensation and Support Authority. The surveys consist of vignette questions selected from legal usage and questions about the victims’ experience of the compensation. The legal rule, about a victim’s right to compensation for the violation, opens up for different interpretations and several possible applications because of its vagueness. It is reminiscent of what H.L.A. Hart describes as “the open texture of law”. If the interpretation and the application of the rule is too standardised, or made from the “external” point of view according to Hart, it can be difficult for the crime victims to get satisfaction by way of the compensation. But if there is no internal point here, or put in another way, if there are merely different personal opinions on and expressions of how the rule is to be applied, it is hard to say that the compensation really can function according to the law. The research topic is therefore linked to the problem of incommensurability and a version of what it means to follow a vague rule in an individual way. Therefore it was interesting that the respondents in general had no difficulty valuing this type of non-pecuniary damage. The main point is that the application of a rule goes beyond the rule and the meaning of the rule is to be understood in reflection of a broader practice. The dissatisfaction among victims can therefore be understood as a consequence of a too narrow understanding of what it means to follow a rule.

The subject and the analysis of the results from the empirical study, show how several dichotomies between formal and informal norms and between the internal and external view of law is put in question and under stress. But this is not meant as a critique, to show a “gap problem” or between “law in books” vis á vis “law in action”, but rather to illustrate that what can be described as leaking law is a central dimension of a normative system that deals with values, languages and the application of general rules through interpretation in a certain context. So the question is rather how its leaks rather than if, moreover, according to the legislator, the estimation of the compensation shall leak.

Purpose:

The aim of the study was to investigate how different types of violations caused by criminal attacks are perceived and valued.

Kränkningsersättning förutsätter enligt lagtexten en ”skada” men det är inte en fysisk eller medicinskt påvisbar personskada som avses, snarare är det den personliga integritetskränkning som brottsliga angrepp kan medföra. Ersättningen är tänkt att ge kompensation för den kränkning som brottet medfört så att brottsoffret får upprättelse. Men är det möjligt att ersätta en sådan upplevelse? Är en kränkning överhuvudtaget något som kan omvandlas till ett skadevärde och ersättas i kronor?

Ett grundproblem är att skadan är av icke-ekonomisk eller ideell natur men ersätts genom pengar. Rättsväsendet har försökt lösa paradoxen genom att ersättningen ska spegla de värderingar och normer som finns i samhället. Traditionellt har man betraktat denna typ av ersättning som alltför subjektiv, att det saknas normer för värderingen av skadan och att det råder en ojämförbarhet mellan skadan och ersättningen. Är det verkligen så illa? Avhandlingens två enkätundersökningar visar att det finns tydliga uppfattningar om ersättningen i samhället och att respondenterna kunde värdera olika typer av kränkningar i pengar. Styrkan i det empiriska resultatet kan därför sägas utgöra en slags vändpunkt i frågan om synen på ersättningens problematik. Avhandlingen visar också att en regel, liknande rätten till kränkningsersättning, inte helt kan ange hur regeln ska tillämpas, men att tillämpningen måste ske i samspel med sin kontext för att fungera som det är tänkt. För att meningsfullt kunna bedöma regeltillämpningen måste man därför ha tillgång till en bred uppfattning om dess ”praxis” – denna avhandling är ett bidrag till en sådan bredare förståelse. Avhandlingen utgår från ett aktuellt och växande rättsområde och den empiriska undersökningen visar att det är både viktigt och möjligt att spegla brottsoffrens behov och omgivningens förväntningar.

Syfte:

Syftet med studien var att undersöka hur olika typer av kränkningar orsakade av brottsliga angrepp uppfattas och värderas. Syftet var också att undersöka hur den kränkningsersättning som utgår till brottsoffer bedöms av såväl brottsoffer som erhållet kränkningsersättning som ett urval av allmänheten. Studien är rättssociologisk och berör teman som allmänt rättsmedvetande, normer, kriminalpolitik och brottsoffer.
Kränkning och upprättelse. En rättssociologisk studie av kränkningsersättning till brottsoffer
Keywords: law enforcement; upprätthållande av lag och ordning; crime victims; brottsoffer; criminal justice system; rättsväsende; legal damages; skadestånd; philosophy; filosofi; money; pengar; Social Norms; Sociala normer; Social Sciences; Samhällsvetenskap; Other Legal Research; Annan rättsvetenskaplig forskning